1979
DOI: 10.1159/000198397
|View full text |Cite
|
Sign up to set email alerts
|

Amylase/Creatinine Clearance Ratio and Tubular Proteinuria in Acute Pancreatitis

Abstract: Amylase/creatinine clearance ratio (CAm/Ccr), urinary protein concentration and urinary protein pattern were studied in 102 samples from 27 patients with acute pancreatitis and in 46 controls. Raised CAm /Ccr, proteinuria and a tubular protein pattern were present in 74, 56 and 96% of the patients, respectively. However, CAm/CCr and proteinuria and CAm/CCr and tubular protein pattern were not correlated. These results do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…This finding of an increased amylase/creatinine clearance ratio in some patients with chronic renal insufficiency agrees with the results of Morton et al (1976) and Lankisch et al (1977). A high amylase/ creatinine clearance ratio has also been reported in severe renal failure (GFR less than 25 ml/min) by Pedersen et al (1976).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding of an increased amylase/creatinine clearance ratio in some patients with chronic renal insufficiency agrees with the results of Morton et al (1976) and Lankisch et al (1977). A high amylase/ creatinine clearance ratio has also been reported in severe renal failure (GFR less than 25 ml/min) by Pedersen et al (1976).…”
Section: Discussionsupporting
confidence: 92%
“…Some authors have reported that the ratio Cam/Ccr remains normal in renal insufficiency (Blainey and Northam, 1967;Levitt et al, 1969) and is increased in the presence of pancreatitis (Mulhausen et al, 1969;Drieling et al 1974;Warshaw and Fuller, 1975). In contrast, recent, studies (Morton et al, 1976;Lankisch et al, 1977) have found raised Cam/Ccr ratios in patients with chronic renal failure without accompanying pancreatitis. These studies measured the clearance of total (T) amylase.…”
mentioning
confidence: 99%
“…Fur thermore, fractional trypsin clearance has been shown to be abnormal in a number of patients with acute and chronic pancreatitis and pancreatic cancer [5,6]. Tubular dysfunction has been demonstrated to be an important factor in determining an altered clearance of both en zymes [7][8][9][10][11][12]. Increased urinary excretion of amylase and immunoreactive trypsin is accompanied by an elevation of one or more indices of tubular impairment.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies in pri mates failed to reveal any appreciable tubular reabsorption of amylase [9], and there is ac cumulating evidence that the tubular pro cessing of amylase differs largely from those of other proteins [2,14,17,27], Recently we have shown that serum amy lase and ACCR increased with advancing age [7]. In the following study we have further analyzed our data and tried to define whether the enhancement of ACCR was of glomerular or tubular origin.…”
mentioning
confidence: 99%